Предмет: Алгебра, автор: serebrakovap43

Пожалуйста помогите с четвёртым заданием​

Приложения:

Ответы

Автор ответа: CbIP0K
1

Ответ:

\frac{(1+\sqrt{zx^{-1} } )^{2}}{1}*\frac{x}{1+\sqrt{zx^{-1} }}=x+\sqrt{zx}

Автор ответа: sergeevaolga5
0

(x^{-1}z+2\sqrt{x^{-1}}\sqrt{z}+1):\frac{1+\sqrt{zx^{-1}}}{x}=\\\\=(\frac{z}{x}+2\sqrt{\frac{z}{x}}+1)*\frac{x}{1+\sqrt{\frac{z}{x}}}=\\\\a=\sqrt{\frac{z}{x}}\\\\=(a^2+2a+1)*\frac{x}{1+a}=\\\\=\frac{(a+1)^2*x}{a+1}=\\\\=(a+1)*x=\\\\=(\sqrt{\frac{z}{x}}+1)*x=\\\\=x(\sqrt{zx^{-1}}+1)

Похожие вопросы
Предмет: Алгебра, автор: bugae82